An optimal incentive contract to avert firm relocation under unilateral environmental regulation - Robert Schmidt; Martin Pollrich; Caroline Stiel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The unilateral introduction of an emissions price can induce firms to relocate to other countries with less stringent environmental regulation. However, firms may be able to reduce the emissions costs in their home country by investing into low-carbon technologies or equipment (abatement capital). Using a two-period model with asymmetric information, we study the optimal design of contracts offered by a regulator who seeks to avert the relocation of a polluting firm to another country. The transfers are contingent on the firm's emissions that are observable to the regulator, and terminate if the firm relocates. We show that under limited commitment, the regulator implements more stringent policies in the first period to induce higher abatement capital investments. This creates a `lock-in effect' that prevents relocation even in the absence of transfers in period 2. We also show that types are not separated if relocation is sufficiently attractive. In practice, the transfers may be implemented via a free allocation of permits if the emissions price arises within an emissions trading scheme.
Keywords: D82; H23; L51; 330